2015
DOI: 10.1002/cpp.1996
|View full text |Cite
|
Sign up to set email alerts
|

Ashamed and Fused with Body Image and Eating: Binge Eating as an Avoidance Strategy

Abstract: Shame is a significant predictor of symptomatology severity of BED patients. Shame significantly impacts binge eating, even controlling for depressive symptoms. Shame significantly predicts body image-related cognitive fusion and eating concern. Body image-fusion and eating concern mediate the link between shame and binge eating. Binge eating may be seen as an avoidance strategy from negative self-evaluations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
53
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 44 publications
3
53
0
1
Order By: Relevance
“…More specifically, Duarte et al (2014), in a study conducted in a nonclinical sample of women from the general population, found that body shame had a significant effect on binge eating symptoms, above overall negative affectivity. Moreover, in a recent study conducted in a clinical sample of women with BED (Duarte et al, 2015a), the effect of shame on the severity of binge eating symptoms was found to be influenced by the extent to which these negative evaluations are associated with cognitive fusion with body image cognitions (Ferreira et al, 2015).…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…More specifically, Duarte et al (2014), in a study conducted in a nonclinical sample of women from the general population, found that body shame had a significant effect on binge eating symptoms, above overall negative affectivity. Moreover, in a recent study conducted in a clinical sample of women with BED (Duarte et al, 2015a), the effect of shame on the severity of binge eating symptoms was found to be influenced by the extent to which these negative evaluations are associated with cognitive fusion with body image cognitions (Ferreira et al, 2015).…”
Section: Introductionmentioning
confidence: 96%
“…Theoretical suggestions (Gilbert, 2002;Goss and Gilbert, 2002) and recent studies indicate that shame feelings, especially those related to body image (Duarte et al, 2015c), play an important role in the prospective development of binge eating symptoms (Dakanalis et al, 2014(Dakanalis et al, , 2015a and in the persistence of binge eating symptoms in patients with BED (Dakanalis et al, 2015b;Duarte et al, 2015a;Jambekar et al, 2003). According to the biopsychosocial model of shame (Gilbert, 1998;Gilbert, 2002Gilbert, , 2003Gilbert, 2007), humans are innately motivated to stimulate positive feelings in others and create a positive image of themselves, to fit within the social group.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hayes et al, 2006). Indeed, psychological inflexibility has been associated with disordered eating (Masuda et al, 2010(Masuda et al, , 2011 and binge eating (Duarte et al, 2015b;Duarte, Pinto-Gouveia and Ferreira, 2014). Additionally, a growing body of research has stressed the pervasive impact of shame (Duarte et al, 2014(Duarte et al, , 2015b and self-criticism (Gilbert, 2002;Goss and Allan, 2009;Goss and Gilbert, 2002) on binge eating and eating psychopathology, which goes beyond the overall negative affect.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, psychological inflexibility has been associated with disordered eating (Masuda et al, 2010(Masuda et al, , 2011 and binge eating (Duarte et al, 2015b;Duarte, Pinto-Gouveia and Ferreira, 2014). Additionally, a growing body of research has stressed the pervasive impact of shame (Duarte et al, 2014(Duarte et al, , 2015b and self-criticism (Gilbert, 2002;Goss and Allan, 2009;Goss and Gilbert, 2002) on binge eating and eating psychopathology, which goes beyond the overall negative affect. Another characteristic that seems to be an important feature of binge eating conceptualization is the dysregulation of satiety and hunger awareness (Sysko et al, 2007) as well as the reactivity to food-related cues (Sobik et al, 2005).…”
Section: Introductionmentioning
confidence: 99%